Strategies for Enhanching Regional Economic Development: A Systematic Literature Review - Vina Dewi Natasari; Inayati Nuraini Dwiputri (Harmoni Economics: International Journal of Economics and Accounting, 2026)
This study aims to analyze regional economic development strategies using a Systematic Literature Review (SLR) approach and the PRISMA method. Research data were obtained from the Scopus database using keywords related to regional economic development strategies. The selection process was conducted through the stages of identification, screening, eligibility, and inclusion, resulting in 20 scientific articles published between 2021 and 2026 as the final sample. The analysis was conducted descriptively, thematically, and comparatively to identify research trends, methodological approaches, and dominant regional economic development strategies. The results indicate that there are six main strategies in regional economic development: developing regional flagship sectors, improving human resource quality, infrastructure development, strengthening investment and the business climate, regional economic digitalization, and multi-stakeholder collaboration. Comparative findings indicate a paradigm shift from conventional approaches focused on the utilization of local resources toward modern approaches emphasizing innovation, digital transformation, the green economy, and collaborative governance. Furthermore, research methods have evolved from descriptive and regression approaches toward the use of spatial analysis, machine learning, and multi-criteria decision-making. Theoretically, these findings reinforce the concepts of regional competitive advantage, human capital, the geography of economic development, and collaborative innovation. Practically, this research implies that local governments need to integrate all dimensions of development strategies to create inclusive, competitive, and sustainable economic growth. Thus, regional economic development strategies in the modern era must be adaptive, innovative, and capable of effectively responding to global dynamics